Three Times a Week Healthy Heart Gymnastics Series-I to Improve Physical Fitness of Elderlies - Fitria, Nita; Lidyana, Lynna; Iskandar, Shelly; Lubis, Leonardo; Purba, Ambrosius (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
The decrease of physical fitness contributes to the morbidity and mortality rates of elderlies. Physical fitness of a person aged 60 years is determined by the level of physical fitness examined through a six minute test. Efforts to improve physical fitness level through sport are needed, one of which is Senam Jantung Sehat Seri-I (Healthy Heart Gymnastics Series-I) with the accurate exercise frequency. The purpose of this study was to analyze the frequency of Senam Jantung Sehat Seri-I that could improve cardiorespiratory fitness in elderlies. This study used pre-experimental method with pre-test and post-test design approach involving 27 healthy elderlies who followed a routine Senam Jantung Sehat Seri-I exercise at the Nursing Home. The research subjects were divided into 3 groups based on the frequency of gymnastics activity per week including 3, 4, and 5 times a week for 6 weeks. Improved physical fitness was determined through the distance traveled by the participants on the 6-minute test at week 1 and week 6. The traveled distance difference was analyzed by using Independent t-test with a p-value 0.05. The elderly group who did Senam Jantung Sehat Seri-I three times a week had a significant mean difference (-106.0; p = 0.009), while groups who performed 4 and 5 times a week exercises did not show significant results. In conclusion, this study provides evidence that Senam Jantung Sehat Seri-I three times a week could improve cardiorespiratory fitness.